Effect of thermal processing on the molecular, structural, and antioxidant characteristics of highland barley β-glucan. (1st November 2021) - Bai, Yi-Peng; Zhou, Hui-Ming; Zhu, Ke-Rui; Li, Qin
Abstract: This present work evaluated the effect of heat fluidization, microwave roasting and baking treatment of highland barley (HB) on the molecular, structural, thermal and antioxidant characteristics of β-glucan. Fluorescence microscopy results showed that heat fluidization exhibited the greatest disruption effect on endosperm cell walls, resulting in the highest extractability (3.35 ± 0.06 g/100 g flour) and purity (92.67 ± 0.73%) of β-glucan. After HB thermal processing, the molecular weight and polydispersity index of β-glucan were respectively reduced by 3.68%–90.35% and 26.45%–39.83%, and its microscopic molecular morphology transformed from large sphere aggregate to alveolate gel network structure. Meanwhile, the structural elucidation by X-ray diffraction and infrared spectroscopy revealed that thermal processing induced the scission of polymeric chain and formation of lattice-type microgels without changing the primary functional groups of β-glucan. Furthermore, thermogravimetry and antioxidant results indicated the thermal stability and antioxidant activity of β-glucan were enhanced by thermal processing. Highlights: Thermal processing caused the destruction of endosperm cell walls. Breaking of cell walls increased the extractability and purity of β-glucan. Thermal processing reduced the molecular weight and polydispersity index of β-glucan. β-glucan changed from sphere aggregate to gel network structure after heat fluidization treatment. Highest increase in antioxidant activity was induced by heat fluidization.